2012
DOI: 10.4049/jimmunol.1103316
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived IL-13Rα1–Positive Thymic Progenitors Are Restricted to the Myeloid Lineage

Abstract: The earliest thymic progenitors (ETPs) were recently shown to give rise to both lymphoid and myeloid cells. While the majority of ETPs are derived from IL-7Rα-positive cells and give rise exclusively to T cells, the origin of the myeloid cells remains undefined. Herein, we show both in vitro and in vivo that IL-13Rα1+ ETPs yield myeloid cells with no potential for maturation into T cells while IL-13Rα1− ETPs lack myeloid potential. Moreover, transfer of lineage-negative IL-13Rα1+ bone marrow stem cells into IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 53 publications
0
41
0
Order By: Relevance
“…C57BL/6 mice were purchased from The Jackson Laboratory (Bar Harbor, ME). IL-13Rα1 +/+ -GFP and IL-13Rα1 −/− C57BL/6 mice were previously described (9). Only female mice were used throughout the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…C57BL/6 mice were purchased from The Jackson Laboratory (Bar Harbor, ME). IL-13Rα1 +/+ -GFP and IL-13Rα1 −/− C57BL/6 mice were previously described (9). Only female mice were used throughout the study.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, we have previously reported that the unipotent attribute of an ETP subset identified in the thymus is tied to expression of the IL-13Rα1 chain (9), which is known to associate with IL-4Rα to form a functional heteroreceptor (HR) through which both IL-4 and IL-13 can signal (11–13). This HR-positive ETP subset (HR + ETP) is restricted to the myeloid lineage and gives rise to CD11b + cells both in vitro when cultured on stromal cells and in vivo when intra-thymically injected into HR-deficient (HR −/− ) mice (9). However, HR + ETPs do not to give rise to T cells either in vitro or in vivo upon intrathymic transfer (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DO11.10/Rag2 −/− transgenic mice (H-2 d ) expressing OVA-specific TCR have been previously described (18). IL-13Rα1-deficient mice in which IL-13Rα1 gene expression was disrupted by deletion of exon 7, 8, and 9 were generated in our lab and have been previously described (17). IL-13Rα1 −/− DO11.10/Rag2 −/− mice have been generated by crossing IL-13Rα1 −/− Balb/c mice with DO11.10/Rag2 −/− mice.…”
Section: Methodsmentioning
confidence: 99%
“…How the function of neonatal DCs and their IL-12 are constrained, resulting in poor neonatal immunity, remains obscure. Because gene disruption of IL-13Rα1 preserves the conventional IL-4R but alters HR expression, we opted to utilize IL-13Rα1-deficient mice (17) to elucidate the physiological mechanism underlying IL-12 cytokine malfunction associated with neonatal DCs. Herein, it is shown that IL-13Rα1-deficient newborn mice dampen Th2 cells yet gain the ability to develop both primary and secondary Th1 immunity.…”
Section: Introductionmentioning
confidence: 99%